2021
DOI: 10.1111/ijcp.14299
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effects of different remineralisation agents on initial enamel lesions by scanning electron microscope and energy‐distributed X‐ray analysis

Abstract: The progression of initial enamel lesions can largely be prevented by early diagnosis and treatment, which aim to protect tooth enamel and dentin. 1 The hard tissues of the teeth are affected by changes in acidity within the oral environment. When the pH falls below 5.5, calcium (Ca) and phosphate (P) ions in the enamel structure migrate away from the tooth tissue, leading to a destructive process known as demineralisation. Without efforts to control the acidification of the oral environment, tooth destruction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The null hypothesis adopted in this study was partially accepted because MI Varnish was the only agent that significantly protected the interproximal reduced enamel surfaces from the simulated cariogenic acidic attack. The storage of the specimens in remineralizing solution for 24 h was carried out because previous research showed that the maximum fluoride and the inorganic components of the MI varnish are released within the first 24 h; moreover, most remineralizing varnishes stay in situ only for 24 h [ 23 ]. Previous reports showed that the acidic challenge adopted in the currently presented experiment succeeded in generating a subsurface demineralized zone of reasonable depth resembling the enamel subsurface lesions obtained using the pH-cycling procedures [ 5 , 6 , 14 , 20 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The null hypothesis adopted in this study was partially accepted because MI Varnish was the only agent that significantly protected the interproximal reduced enamel surfaces from the simulated cariogenic acidic attack. The storage of the specimens in remineralizing solution for 24 h was carried out because previous research showed that the maximum fluoride and the inorganic components of the MI varnish are released within the first 24 h; moreover, most remineralizing varnishes stay in situ only for 24 h [ 23 ]. Previous reports showed that the acidic challenge adopted in the currently presented experiment succeeded in generating a subsurface demineralized zone of reasonable depth resembling the enamel subsurface lesions obtained using the pH-cycling procedures [ 5 , 6 , 14 , 20 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been discovered that using toothpaste that contains HAP causes HAP crystals to adhere to the tooth surface, repair it, and fill in the pitted regions [ 38 ], whereas using F toothpaste did not fix any of the enamel surface imperfections. Studies demonstrated that teeth treated with HAP toothpaste had considerably greater calcium contents than untreated ones [ 46 ]. Surface hardness was also used as a reference to estimate the elemental composition of the teeth.…”
Section: Nanomaterialsmentioning
confidence: 99%
“…Calcium glycerophosphate (CaGP) and Xylitol-containing gel (R.O.C.S Medical Mineral Gel, DRC Group, Moscow, Russia) show remineralizing effect by increasing the mineral content on dental enamel has been reported (14). CaGP demonstrates a preventive action against demineralization by enhancing the resistance of hydroxyapatite crystals (15).…”
Section: Different Remineralization Agents On Artificial Caries Lesionmentioning
confidence: 99%